PENGARUH UPAH SEKTOR INDUSTRI, TINGKAT PENDIDIKAN, DAN INVESTASI ASING TERHADAP PENYERAPAN TENAGA KERJA SEKTOR INDUSTRI DI INDONESIA - Usman, Agung Febrian; Sentosa, Sri Ulfa (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
Abstract: This research aims to examined the effect of industry of wage, education and forigninvestment on the agricultural sector labor industry in Indonesia with the selected model is the RandonEffect Model (REM ). The data used is panel data during the period 2014-2018, with thw twchnique ofcollecting documentation data and library studies obtained fromm relevant institution and agencies.Thevariables use are industry of wage (X1), education (X2), foreign invesment (X3), . the research methodused is Ordinary Least Square (OLS). The estimation result show that industry of wage have a positiveand its significant effect on the agricultural sector labor industry in Indonesia. Education have anegative and significant effect on the agricultural sector labor industry in Indonesia. foreign investmenthave a positife and its siknificant effect the agricultural sector industry Indonesia. Meanwhilesimultaneously industry of wage, education and foreign investment effect the agricultural sector laborindustry in Indonesia.Keywords: Agricultural Sector Labor Industry, Industry Of Wage, Education, Foreign Investment, andOrdinary Least Square (OLS)